Life cycle assessment of urban wastewater systems: Quantifying the relative contribution of sewer systems. (15th June 2015) - Risch, Eva; Gutierrez, Oriol; Roux, Philippe; Boutin, Catherine; Corominas, Lluís
Abstract: This study aims to propose a holistic, life cycle assessment (LCA) of urban wastewater systems (UWS) based on a comprehensive inventory including detailed construction and operation of sewer systems and wastewater treatment plants (WWTPs). For the first time, the inventory of sewers infrastructure construction includes piping materials and aggregates, manholes, connections, civil works and road rehabilitation. The operation stage comprises energy consumption in pumping stations together with air emissions of methane and hydrogen sulphide, and water emissions from sewer leaks. Using a real case study, this LCA aims to quantify the contributions of sewer systems to the total environmental impacts of the UWS. The results show that the construction of sewer infrastructures has an environmental impact (on half of the 18 studied impact categories) larger than both the construction and operation of the WWTP. This study highlights the importance of including the construction and operation of sewer systems in the environmental assessment of centralised versus decentralised options for UWS. Graphical abstract: Highlights: We assess the environmental impacts of sewer systems and compare to those of WWTPs. Many studies on urban wastewater systems are based on incomplete sewer inventories. The sewer system has larger impacts than the WWTP on some impact categories. Construction materials and civil works should be included in sewers' inventories.